Whistleblower protection act 2010: a comparative study on the viability of legislation in protecting the rights of whistleblower / Rose Azureen Rostarizam … [et al.] - Rostarizam, Rose Azureen; Muhamad Fadzil, Fatinizyan; Zakaria, Amalia Aina; Ramli, Azizul Hakim (2014)
This project paper would cover firstly on the protection of whistleblower in our country Malaysia. The second chapter would cover in dept all the protection provided in country in Malaysia, United Kingdom and United States. This chapter would explore all the legal protection cover in this three country. While in Chapter three, in order to identify it effectiveness we would compare it with developed country in whistleblower such as United Kingdom and United States. This chapter would show all the weaknesses and strength of each country in protecting the legal right of a whistleblower. The strength showed by he three country shall be a recommendation to be followed and weaknesses as well as loopholes should be improved. The comparison will showed the loopholes of protection of whistleblower in our country and this research should help to improve our whistleblower protection act 2010. Next chapter would cover on the guidelines for effective legislation provided in United States and United Kingdom that could be followed by our country. This chapter would emphasis on the importance of the study of effectiveness and the impact on the whistleblower protection in our country. The last chapter would cover on the recommendation that should be followed by our country, Malaysia in order to improve our legislation regarding the protection of whistleblower and to provide the best whistleblower protection Act that can protect their right not only internally but also externally. The last chapter is wrapped up in order to encourage people to whistle blowing and to show the benefits of whistle blowing. Thus, for them to involve in whistle blowing the protection provided shall be improve.